Neural oscillations and memory: unraveling the mechanisms of anesthesia-induced amnesia - Liu, Hui; Yang, Zhanfei; Chen, Yuxuan; Yang, Fei; Cao, Xue; Zhou, Gao; Zhang, Yu (Frontiers in Neuroscience, 2024)
General anesthesia is a widely used medical practice, affecting more than 300 million patients annually. Despite its ubiquity, the underlying mechanisms through which anesthetic agents induce amnesia remain poorly understood. This review explores the impact of general anesthetics on memory function, with a particular focus on the role of neural oscillations in anesthesia-induced memory suppression. Neural oscillations, such as theta, gamma, delta oscillations, slow oscillations (SO), spindles, and sharp wave ripples (SWR), are critical for memory formation and consolidation. Various anesthetics modulate these oscillations in ways that affect memory, even at subanesthetic concentrations. We highlight recent findings on the molecular and electrophysiological mechanisms by which general anesthetics influence memory-related neural oscillations, including the inhibition of synaptic plasticity, alterations in spike-timing-dependent plasticity (STDP), and disruption of cross-frequency couplings like theta-gamma and SO-spindle-SWR. Additionally, the review addresses the significance of age in anesthesia-related memory loss, with elderly patients being particularly vulnerable to long-term cognitive decline. Electrophysiological techniques, such as Electroencephalography (EEG); and advanced neuromodulation techniques, such as chemogenetics, and optogenetics, have provided insights into the neural dynamics underpinning anesthesia-induced amnesia, yet the causal relationship between EEG rhythms and memory impairment remains to be fully elucidated. This review underscores the importance of further research into the interaction between anesthesia, neural oscillations, and memory. Understanding these mechanisms will not only advance theoretical knowledge of general anesthesia but also aid in the development of safer anesthetic strategies to mitigate postoperative cognitive dysfunction, especially in high-risk populations.